The effect of toothpaste containing Kayu Sugi Extract on plaque formation - Witjaksono, Widowati (Airlangga University, 2000)
Background: Although many researches had revealed the beneficial effect of Kayu Sugi as a chewing stick, study on the effectiveness of its extract in toothpaste is still inadequate. Purpose: The objective of this study was to compare the effect of toothpaste, with and without Kayu Sugi extract on preventing plaque formation. Methods: The study consists of two sessions which was separated by three days washout period. The subjects were given two types of toothpaste, with and without Kayu Sugi extract to be used in the first and second session separately. The subjects were polished and plaque score were measured after one hour for the first quadrant, two hours later for the second quadrant and after four hours for the third/fourth quadrant. Subjects were not allowed to eat, drink or rinse during this four hours period. The procedures were repeated for the second session after three days washout period. The plaque score were recorded as absent (code 0) and present (code 1), and only labial and palatal/lingual surfaces of each tooth were used for plaque scoring. Result: The study showed that there was no significant difference of the amount of plaque formed after polishing using two different toothpastes, with and without Kayu Sugi extract. Conclusion: We concluded that toothpaste with or without Kayu Sugi extract give similar level in preventing plaque formation.